Effects of SBS and different natural asphalts on the properties of bituminous binders and mixtures - Yılmaz, Mehmet; Çeloğlu, Muhammed Ertuğrul (My University, 2013)
In this study, three different natural asphalts (Trinidad Lake Asphalt, Iranian gilsonite and American gilsonite) and styrene–butadiene–styrene (SBS) were used as additive in bitumen modi?cation. Results of binder tests showed that addition of 10.0% American gilsonite (MB 10%AG ), 9.5% Iranian gilsonite (MB 9.5%IG ), 60% Trinidad Lake Asphalt (TLA) (MB 60%TLA ) and 3.8% SBS (MB 3.8%SBS ) to pure bitumen (PG 58-34) achieved the desired performance level (PG 70-34). Experiments conducted on mixtures showed that mixtures prepared with MB 60%TLA had the highest stiffness, stability, tensile strength and resistance to fatigue and permanent deformation. On the other hand, mixtures prepared with MB 9.5%IG and MB 3.8%SBS were observed to have highest resistance to moisture induced damage.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Hot mix asphalt; Modification; Natural asphalt; Styrene–butadiene–styrene